Inclusion of palliative care in health care policy for older people: A directed documentary analysis in 13 of the most rapidly ageing countries worldwide - Pivodic, Lara; Smets, Tinne; Gott, Merryn; Sleeman, Katherine E; Arrue, Borja; Cardenas Turanzas, Marylou; Pechova, Karolina; Kodba Čeh, Hana; Lo, Tong Jen; Nakanishi, Miharu; Rhee, YongJoo; Ten Koppel, Maud; et al. (Palliative medicine, 2021)
BACKGROUND: Palliative care is insufficiently integrated in the continuum of care for older people. It is unclear to what extent healthcare policy for older people includes elements of palliative care and thus supports its integration. AIM: (1) To develop a reference framework for identifying palliative care contents in policy documents; (2) to determine inclusion of palliative care in public policy documents on healthcare for older people in 13 rapidly ageing countries. DESIGN: Directed documentary analysis of public policy documents (legislation, policies/strategies, guidelines, white papers) on healthcare for older people. Using existing literature, we developed a reference framework and data extraction form assessing 10 criteria of palliative care inclusion. Country experts identified documents and extracted data. SETTING: Austria, Belgium, Canada, Czech Republic, England, Japan, Mexico, Netherlands, New Zealand, Singapore, Slovenia, South Korea, Spain. RESULTS: Of 139 identified documents, 50 met inclusion criteria. The most frequently addressed palliative care elements were coordination and continuity of care (12 countries), communication and care planning, care for family, and ethical and legal aspects (11 countries). Documents in 10 countries explicitly mentioned palliative care, nine addressed symptom management, eight mentioned end-of-life care, and five referred to existing palliative care strategies (out of nine that had them). CONCLUSIONS: Health care policies for older people need revising to include reference to end-of-life care and dying and ensure linkage to existing national or regional palliative care strategies. The strong policy focus on care coordination and continuity in policies for older people is an opportunity window for palliative care advocacy.
Keywords: Health Policy; Humans; Belgium; Singapur; Anglie; Netherlands; zdravotní politika; Palliative Care; Japonsko; Korejská republika; Nizozemsko; Aged; stárnutí; health policy; Spain; senioři; lidé; Aging; Rakousko; Japan; documentary analysis (not a MeSH heading; research design used); Španělsko; Republic of Korea; Singapore; England; New Zealand; Austria; Canada; Belgie; Kanada; Delivery of Health Care; Nový Zéland; poskytování zdravotní péče; paliativní péče; older people (not a MeSH heading but important identifier of population); palliative care